ISPC Note on the CGIAR Strategic Results Framework - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2010)
This document was prepared as an input to the CGIAR e‐conference 30 June‐ 2 July 2010.